Management Training Program and Leadership Mental Development for Field Staff of PT Intan Pertiwi Industri - Amrin Soamole; Dwi Novita Sari (MultiTech Publisher, 2024)
Management Training and Leadership Mental Coaching Program at PT INTIWI aims to enhance managerial skills and the mental well-being of field personnel. Against the backdrop of understanding the complexity of fieldwork and the increasingly dynamic market demands, this program is designed to cultivate outstanding field leaders. Training methods involve discipline training, case-based training, pre-tests, and post-tests. Evaluation is conducted through pre-tests and post-tests, as well as participant feedback and field performance monitoring. The program is expected to have a positive impact, such as increased productivity, job satisfaction, and a reduction in stress levels. The success of this program will create a more balanced work environment and contribute to the strategic goals achievement of PT INTIWI.